Hierarchical nanowires for high-performance electrochemical energy storage - 李硕 董轶凡 王丹丹 陈伟 黄磊 石长玮 麦立强 (Frontiers of physics, 2014)
Nanowires are promising candidates for energy storage devices such as lithium-ion batteries, supercapacitors and lithium-air batteries. However, simple-structured nanowires have some limitations hence the strategies to make improvements need to be explored and investigated. Hierarchical nanowires with enhanced performance have been considered as an ideal candidate for energy storage due to the novel structures and/or synergistic properties. This review describes some of the recent progresses in the hierarchical nanowire merits, classification, synthesis and performance in energy storage applications. Herein we discuss the hierarchical nanowires based on their structural design from three major categories, including exterior design, interior design and aligned nanowire assembly. This review also briefly outlines the prospects of hierarchical nanowires in morphology control, property enhancement and application versatility.